3D bioprinting of mineralizing cyanobacteria as novel approach for the fabrication of living building materials - Reinhardt, Olena; Ihmann, Stephanie; Ahlhelm, Matthias; Gelinsky, Michael (Frontiers in Bioengineering and Biotechnology, 2023)
To develop Living Building Materials (LBM), the process of three-dimensional (3D) bioprinting was investigated. For this purpose, an alginate-methylcellulose-based hydrogel with a sea sand content of up to 50 wt% was analyzed, incorporating the cyanobacterium Synechococcus sp. strain PCC 7002 as the living component, which is capable of calcium carbonate (CaCO3) biomineralization. Initially, the viability of the cells immobilized in the scaffolds was confirmed over 14 days, showing that the cells were able to withstand shear stress and pressure during the extrusion process and remain viable in the immobilized state. After confirming the biomineralization of PCC 7002 in liquid culture, the mineralizing capacity was tested in the immobilized state in the bioprinted LBM and analyzed concerning their mechanical and structural properties. An increase in the compressive strength of the LBM was measured in the samples with live cyanobacteria compared to those without cells. Scanning electron micrographs and energy-dispersive X-ray spectroscopy confirmed the formation of CaCO3, mainly on the outer surface of the LBM. Bioprinted mineralized LBM containing photosynthetically active microorganisms could prove beneficial for designing environmentally friendly construction materials.